The Impact of the COVID-19 Pandemic on College Student's Stress and Physical Activity Levels - Jonathan R. Anderson; Myra J. Bloom; Gladys Y.X. Chen; Scarlet R. Jost; Donald P. Keating III; Andrew S.I.D. Lang; Nancy V. Mankin; Ericka R. McMahan; Jonathan A. Merheb; Philip P. Nelson; Joshua C. Nnaji; Enrique F. Valderrama-Araya (The Ohio State University Libraries, 2022)
Background: The coronavirus disease 2019 (COVID-19) pandemic adversely disrupted university student educational experiences worldwide, with consequences that included increased stress levels and unhealthy sedentary behavior. Aim: This study aimed to quantify the degree of impact that COVID-19 had on the levels of physical activity and stress of university students by utilizing wearable fitness tracker data and standard stress survey instrument scores before and during the pandemic. Methods: We collected Fitbit heart rate and physical activity data, and the results of a modified Social Readjustment Rating Scale (SRRS) stress survey from 2,987 university students during the Fall 2019 (residential instruction; before COVID-19) and Fall 2020 (hybrid instruction; during COVID-19) semesters. Results: We found indicators of increased sedentary behavior during the pandemic. There was a significant decrease in both the levels of physical activity as measured by mean daily step count (↓636 steps/day; p = 1.04 · 10-9) and minutes spent in various heart rate zones (↓58 minutes/week; p = 2.20 · 10-16). We also found an increase in stressors during the pandemic, primarily from an increase in the number of students who experienced the "death of a close family member" (38.8%), with the number even higher for the population of students who opted to stay home and attend classes virtually (41.4%). Conclusions: This study quantifies the decrease in levels of physical activity and notes an increase in the number of students who experienced the death of a close family member, a known stressor, during the first year of the COVID-19 pandemic. These findings allow for more informed student-health-focused interventions related to the COVID-19 pandemic disruptions experienced by academic communities worldwide.